ASSOCIATION BETWEEN OSTEOPOROSIS AND AGE, PHYSICAL ACTIVITY, AND OBESITY IN ELDERLY OF TULIKUP VILLAGE, GIANYAR - Juwita, Ratna (WMJ (Warmadewa Medical Journal), 2018)
The proportion of elderly population in Tulikup Village, Gianyar Regency is 0.72%. One of the potential disease affecting this aging population is osteoporosis. Morbidity of osteoporosis could impose future burden to community and government in term of medical, social and financial implications. The present study determined prevalence and risk factors of osteoporosis to provide solid basis for the development of screening model. Cross sectional study was conducted and 221 of 649 people aged â¥45 were randomly sampled by multi-stage random sampling method. Examined variables were osteoporosis treated as dependent variable and several independent variables: age groups, gender, personal history of fracture, dietary calcium intake, physical activity, alcohol & phosphorus intake, body mass index (BMI), parental history of fracture, diabetes mellitus, and smoking habit. Data was analyzed statistically by univariate, bivariate (chi square), and multivariate (logistic regression) analysis. The prevalence of osteoporosis in eldery was 28.1% (26.0% in women and 30.6% in men) and the rest was osteopenia (54.3%). Multivariate analysis showed that prevalence ratio (PR) of osteoporosis in relation to obesity, elderly group, post elderly group, and vigorous physical activity were 0.3 (CI 95%: 0.1-0.9), 4.5 (CI 95%: 1.4-1.9), 6.2 (CI 95%: 1.8-20.9), and 0.5 (CI 95%: 0.2-0.9), respectively. In general, obesity and vigorous physical activity significantly decreased the risk of osteoporosis. Obesity decreased the risk of having osteoporosis by 70% and vigorous physical activity deceased the risk of osteoporosis by 50% . Being elderly and post elderly increased the risk of having osteoporosis significantly. Elderly group was 4.5 times more likely to have osteoporosis, furthermore post elderly group increased the risk of by 6.2 times.